2001
DOI: 10.1210/jc.86.3.1008
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 Aldosterone Synthase Deficiency Presenting in a Middle-Aged Man

Abstract: Aldosterone synthase deficiency due to mutations in the CYP11B2 gene usually presents in infancy with electrolyte abnormalities and failure to thrive, whereas affected adults are usually asymptomatic. We describe a patient who first came to medical attention in middle age when he developed hyperkalemia after preparation for a barium enema. Past medical history was notable for failure to thrive in infancy. He had elevated PRA with low serum and urinary levels of aldosterone and its metabolites and normal or sli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 0 publications
1
12
0
1
Order By: Relevance
“…Our data are in line with observations in humans with type 1 aldosterone deficiency, who are usually still able to adapt renal K + excretion and to stay more or less in K + balance. 38 Likewise, adrenalectomized animals 23,24,39 were shown to augment renal K + excretion in response to an increased dietary K + intake, although usually at the expense of more or less elevated plasma K + levels. Previous studies on adrenalectomized rats and rabbits indicated that a high-K + diet increases renal Na + and K + channel activities independent from aldosterone.…”
Section: Discussionmentioning
confidence: 99%
“…Our data are in line with observations in humans with type 1 aldosterone deficiency, who are usually still able to adapt renal K + excretion and to stay more or less in K + balance. 38 Likewise, adrenalectomized animals 23,24,39 were shown to augment renal K + excretion in response to an increased dietary K + intake, although usually at the expense of more or less elevated plasma K + levels. Previous studies on adrenalectomized rats and rabbits indicated that a high-K + diet increases renal Na + and K + channel activities independent from aldosterone.…”
Section: Discussionmentioning
confidence: 99%
“…2A). Sequencing of CYP11B2 in the patient also identified a heterozygous C to A change at codon thase deficiency type 1 [2,[3][4][5][6]12]. Furthermore, several missense mutations (S315R, L324Q, R374W, R384P, L451F, and L461P) have been identified in type 1 patients.…”
Section: Resultsmentioning
confidence: 87%
“…Aldosterone synthase deficiency type 1 is caused by mutations in CYP11B2 that completely abolish enzymatic activity [3][4][5][6]. In contrast, aldosterone synthase deficiency type 2 is characterized by low aldosterone levels, increased 18OHB and 18OHDOC levels, and an increased 18OHB/aldosterone ratio.…”
mentioning
confidence: 99%
“…Elles se traduisent cliniquement par des épisodes de déshydratation extracellulaire avec retard staturo-pondéral, s'améliorant un peu avec l'âge. Un cas a pu être rapporté chez l'adulte [37]. Les activités enzymatiques 18 hydroxylase et 18 oxydase sont portées par un complexe possédant également une faible activité 11 hydroxylase codée par le gène CYP11B2.…”
Section: Hyperréninisme Hypoaldostéronisme Isoléunclassified